ANALISIS KUALITAS PELAYANAN DI BADAN PENANAMAN MODAL DAN PELAYANAN PERIJINAN TERPADU (BPMPPT) KABUPATEN JEPARA - Hartanto, Wahyu Tri; Hariani, Dyah (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Nowadays,we still find some weakness services in Indonesia,the weakness is a complicated service, inefficient, lack of fair service in giving service, and many factors which influence the service itself,such as from society, staffs' ability, regulations set and supporting facilities. The aim of this study is to analyze the service quality and also to know some factors which hold up in giving service in BPMPPT in Jepara regency. This is a descriptive qualitative research. The data was taken by interview,observation,and documentation. To measure the quality service,the writer used five indicators, there are Tangibles, Reliability, Responsivess, Assurance, Emphaty. To know obstacles in giving service, the writer used five indicators, there are Gap Persepsi Manajemen, Gap Persepsi Kualitas, Gap penyelenggaraan Pelayanan, Gap komunikasi pasar, Gap kualitas pelayanan. The result of this research shows that in BPMPPT in Jepara there are some services that not work properly, they are infrastucture, time employee dicipline, and the lateness of time issue of licensing. Meanwhile the obstacles is the lackness of staff and thw society who wants the quick process.